UTILIZATION OF PALM OIL MILL LIQUID WASTE (POME) AS AN ALTERNATIVE FUEL BIO COMPAC NATURAL GAS OR BIO-CNG - Al Ramzi; T. Rovida Kamal; M. Yusuf (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Indonesia faces crucial challenges in energy security due to the increasingly alarming decline in oil reserves from around 3.6 billion barrels in 2000 to less than 2.5 billion barrels in 2023, while dependence on oil imports continues to burden the national energy balance and economy. Amid unstable global geopolitical conditions, including the Russia-Ukraine war and tensions in the Middle East that have caused fluctuating energy prices, the transition to local and sustainable energy sources has become a strategic priority. The Indonesian government has affirmed its commitment to achieving net-zero emissions by 2060 through various energy transition policies, including the development of renewable gas and the utilization of waste as an energy source. One of the major potentials that has not been optimally utilized is palm oil mill effluent (POME), which annually produces more than 500 million tons throughout Indonesia. POME contains a high concentration of organic matter that can be processed through anaerobic digestion to produce biogas, which is then purified and compressed into Bio-Compact Natural Gas (Bio-CNG). This study analyzes the potential of Bio-CNG technology from POME in three main dimensions: (1) conversion and storage technology, (2) economic analysis and feasibility of scale implementation at the palm oil mill level, and (3) its contribution to reducing GHG emissions and diversifying national energy. The study results show that by utilizing 70% of the total annual POME, the potential for Bio-CNG production reaches over 3.5 billion m³/year, equivalent to over 25% of current domestic natural gas consumption. Furthermore, the application of this technology can reduce CH3 emissions.₄from POME waste up to 80% and contributes significantly to the target of renewable energy (EBT) mix of 23% in 2025 and net zero in 2060. Economically, Bio-CNG shows competitive production costs (Rp25,000–35,000/m³) compared to industrial gas prices, especially with the presence of carbon incentives and carbon pricing mechanisms that are being developed. This study concludes that converting POME into Bio-CNG is not only a green technology solution but also a crucial energy security and climate mitigation strategy amidst uncertain global energy supplies and international decarbonization pressures. Policy recommendations include tax incentives, integration into the national gas grid, and mandatory regulation of waste energy utilization for the palm oil industry.